'Harvest work, migration, and the structured phenomenology of time' - Karen OReilly; Sam Scott (2022)
The paper draws on Rosa’s three dimensions of the structured phenomenology of time – daily time, longer time, and historical time – as a conceptual lens to analyse the lived experiences and structural framing of temporary farm work in the UK and to address the question: how is it that short-term precarious work remains the accepted solution for agricultural work even under conditions that challenge the status quo. We draw on qualitative research with farmers and workers conducted prior to and during Brexit and Covid-19. We note that farmers and workers alike have found ways to accept and adjust to seasonal migrant labour as a taken-for-granted solution to the pressures of daily farm life. Further, farmers contend that seasonal migrant work is essential to secure the longer-term viability of their farms, while migrant workers’ longer-term view involves delayed gratification in a ‘dual frame of reference’. Local workers, alternatively, cannot imagine farm work as providing a long-term future. When looking historically at farm life, farmers and workers alike invoke changing epochs, to explain current conditions as the conditions of our times, and thus to deny their own agency. Structuraleconomic shifts are thus never addressed and other ways of doing things never imagined.